2001
DOI: 10.1063/1.1334921
|View full text |Cite
|
Sign up to set email alerts
|

Orientation dependence of blistering in H-implanted Si

Abstract: The orientation effect on blistering phenomenon in H implanted Si was studied for (100), (111), and (110) Si wafers. It was found that substrate orientation has no observable effects on the underlying blistering mechanisms. Furthermore, the implantation damage, Si–H complex formation in as-implanted samples and surface roughness of the transferred layer appeared to be unaffected by the orientation. However, the blistering kinetics are orientation dependent, with (100) Si having the fastest blistering rate, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
45
1

Year Published

2001
2001
2008
2008

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 66 publications
(48 citation statements)
references
References 17 publications
2
45
1
Order By: Relevance
“…Earlier results presented by Höchbauer et al 2 and Zheng et al 9 showed that the lattice damage produced by H ion implantation into Si results in the formation of an in-plane biaxial compressive ͑negative͒ stress. Höchbauer observed the correlation between the platelet and damage distribution 10,11 and proposed that the out-of-plane tensile strain zz that would accompany an in-plane compressive stress xx = yy , would be peaked at the location of maximum damage and that the strain assists in nucleating Si-H defects that evolve into H platelets.…”
Section: Tamzin Laffordmentioning
confidence: 94%
“…Earlier results presented by Höchbauer et al 2 and Zheng et al 9 showed that the lattice damage produced by H ion implantation into Si results in the formation of an in-plane biaxial compressive ͑negative͒ stress. Höchbauer observed the correlation between the platelet and damage distribution 10,11 and proposed that the out-of-plane tensile strain zz that would accompany an in-plane compressive stress xx = yy , would be peaked at the location of maximum damage and that the strain assists in nucleating Si-H defects that evolve into H platelets.…”
Section: Tamzin Laffordmentioning
confidence: 94%
“…This hypothesis is strengthened by previous studies on the effect the silicon wafer orientation has on surface blister formation kinetics. [155] The study showed, that in H-implanted silicon wafers of different crystal orientation, the surface blister formation kinetics are controlled by the number of Si-Si bonds, that need to be broken to form popped-off surface blisters.…”
Section: As-implantedmentioning
confidence: 99%
“…Recent work by Nastasi et al 6 showed that the platelet orientation in both H ion implanted and plasma hydrogenated Si could be explained by a Volmer-type nucleation model that accounted for the in-plane compressive stress that is present in the implanted material. 7,8 Since the stress in ion implanted materials results from radiation defects, it is unclear if the model proposed by Nastasi et al is also appropriate for situations where an external stress is introduced by other means. In this work, we explore platelet formation and surface exfoliation in plasma hydrogenated single crystalline Si where a region of plane-stress is introduced by a buried SiGe strain layer.…”
mentioning
confidence: 99%